2022
DOI: 10.3390/pharmaceutics14050933
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Tool for Assessing the Environmental Impact of 3D Printing Technologies: A Pharmaceutical Perspective

Abstract: Technological advancements have created infinite opportunities and rendered our life easier at several fronts. Nonetheless, the environment has suffered the aftermaths of modernization. Ironically, the pharmaceutical industry was found to be a significant contributor to environmental deterioration. To tackle this issue, continuous eco-evaluation of newly introduced technologies is crucial. Three-dimensional printing (3DP) is rapidly establishing its routes in different industries. Interestingly, 3DP is revolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Two articles in our analysis did not focus on biologics. One of these papers, Youssef et al (2022), reported a novel environmental impact assessment tool (Index of Greenness Assessment of Printed Pharmaceuticals (iGAPP)) for 3D printing in the pharmaceutical sector, and specifically 3D printing that personalises therapeutics through individually adjusted doses (94). The second paper, Sharma…”
Section: Resultsmentioning
confidence: 99%
“…Two articles in our analysis did not focus on biologics. One of these papers, Youssef et al (2022), reported a novel environmental impact assessment tool (Index of Greenness Assessment of Printed Pharmaceuticals (iGAPP)) for 3D printing in the pharmaceutical sector, and specifically 3D printing that personalises therapeutics through individually adjusted doses (94). The second paper, Sharma…”
Section: Resultsmentioning
confidence: 99%
“…The powder is finally sintered by softening a thermoplastic polymer [ 36 ]. A major advantage of this technology is the single-step printing process accompanied by high resolution without using an organic solvent [ 37 ]. However, it still retains the possibility of pharmaceutical agent degradation as a result of laser sintering [ 38 ].…”
Section: Techniques For Fabricating Drug Delivery Vehiclesmentioning
confidence: 99%